The Effects of Stimulation on Children Experiencing Developmental Disorders - Rachmah, Siti; Soedirham, Oedojo; Fatah, Muhammad Zainal (Health Notions, 2018)
The important period of the child growth and development is the time when a  child is at the age of 0-5 because the abilities in language, creativity, social awareness  emotion, and intelligence develop very rapidly and function as the base for the next  developmental stages. Approximately 5-10% of children experience developmental  delay. This observational analytical study was conducted in a cohort design using longitudinal or time period approach. Questionnaires were used to collect the primary  data. The method used to choose the samples was consecutive sampling. Moreover, data analysis was done by using multiple logistic regression test. The results of this study showed that the dominant developmental disorder happening to the children under five was speech delay. The results of analysis using multiple logistic regression test showed that there were significant effects of stimulation on gross motor p = 0.034, on fine motor p = 0.037, on speech and language p = 0.036, and on social independence.p = 0.036. Thus, there were significant effects of stimulation on developmental disorder.      Keywords: Stimulation, Developmental disorder, Children